Encouraging ecological behaviour through induced hypocrisy and inconsistency. (September 2016) - Priolo, Daniel; Milhabet, Isabelle; Codou, Olivier; Fointiat, Valérie; Lebarbenchon, Emmanuelle; Gabarrot, Fabrice
Abstract: Remembering one's past transgressions of a social norm is known as an effective paradigm for enhancing pro-social and ecological behaviours. Our study aimed to show that reminding one's norm transgressions can arise cognitive dissonance and can lead to behavioural change as induced hypocrisy does. In particular, we tested whether inconsistency between the self-concept and the remembered past transgressions is or is not likely to encourage behavioural change. To reach this goal, we conducted an experiment comparing induced hypocrisy, injunctive inconsistency and descriptive inconsistency with five comparison conditions. The results showed that, as observed with the induced hypocrisy paradigm, presenting a salient injunctive norm and its past transgressions enhances psychological discomfort, actual donation and donation amounts for an ecological association. The discussion addresses applied perspectives and theoretical implications. Highlights: Reminding one's transgressions of social norms generates cognitive dissonance. Comparison of normative inconsistencies and induced hypocrisy. Injunctive inconsistency and induced hypocrisy produce the greatest discomfort. Cognitive dissonance can favour actual donations to an ecological association.